Protecting lives & livelihoods: interrogating the abuse of human rights in the midst of a global pandemic - Thomas Prehi Botchway; Linda Peasah Owusu (Cogent Social Sciences, 2024)
This study attempts to review some of the measures countries implement to mitigate the upsurge of the corona virus disease (Covid-19). It delves into how the Ghanaian state abused its powers in the name of ‘protecting lives and livelihoods’. It focuses on the introduction and subsequent implementation of draconian measures that infringe on the rights of the citizen and how the state (government) abuses its authority under such conditions. The study uses Ghana’s implementation of COVID-19-related measures as a case. Thus, the various directives of the president and state agencies are reviewed. Key among the issues is the use of emergency powers as granted by the 1992 Constitution of Ghana and the introduction of executive instruments that ultimately curtailed citizens’ rights. The Imposition of Restrictions Act, 2020 (Act 1012), Article 21 (4) (c) & (d) as well as Article 31 of the 1992 Constitution of Ghana, Section 169 of the Public Health Act, 2012 (Act 851), etc. are among some of the legal sources that are interrogated by the study. In addition, the ban on public gatherings (religious, social, and political) is questioned from the perspective of human and other related rights citizens enjoy. The study thus examines the rationale behind the use of emergency powers during the COVID-19 pandemic and how such exercise of powers affects the rights and freedoms of citizens (the very people that such exercise of power is meant to protect).